Eternal life : a novel - Horn, Dara, 1977- (W.W. Norton & Company, 2018)
Ever since she made a deal to save her son's life in Roman-occupied Jerusalem, Rachel has been doomed to live eternally, but as her descendants develop new technologies for immortality, she realizes that, for them to live fully, she must die.